Chemotactic Motility and Growth of Pseudomonas fluorescens Towards Glucose Concentration - ENDAH ROSA; UMMI MARDHIAH BATUBARA; SUPARJO SUPARJO (Microbiology Indonesia, 2019)
Pseudomonas fluorescens is plant growth promoting rhizobacteria (PGPR) often inoculated on plants as natural biocontrol agent capable of protecting the plants from soil-borne pathogens. Chemotactic motility allows populations of P. fluorescens to rapidly search for nutrients and is an important factor determining their competitive success to colonize plant root. Therefore, we investigated various glucose concentrations from 0% to 1% (w/v) to enhance chemotactic motility and growth of this rhizobia. Chemotactic motility was evaluated using swim plate assay and bacterial growth was measured using UV-Vis Spectrophotometer in LB and M9 medium. Glucose with low concentration (0.05%) showed to have optimum response in P. fluorescens chemotactic motility with colony diameter 38.3 mm in LB medium and 12.8 mm in M9 medium. Highest growth of P. fluorescens was seen in control condition of LB medium reaching a peak at 0.0246 OD600 (~Â±1,44x107 CFU ml-1 ) while growth in M9 medium supplemented with 1% glucose was just slightly lower with 0.0227 OD600 (~Â±1,32x107 CFU ml-1). Glucose in high concentration showed to repress chemotactic motility and first growth phase of P. fluorescens in LB medium due to catabolite repression.